ATP dynamics as a predictor of future podocyte structure and function after acute ischemic kidney injury in female mice - Masahiro Takahashi; Shinya Yamamoto; Shigenori Yamamoto; Akihiro Okubo; Yasuaki Nakagawa; Koichiro Kuwahara; Taiji Matsusaka; Shingo Fukuma; Masamichi Yamamoto; Michiyuki Matsuda; Motoko Yanagita (Nature Communications)
Abstract Acute kidney injury (AKI), typically caused by ischemia, is a common clinical complication with a poor prognosis. Although proteinuria is an important prognostic indicator of AKI, the underlying causal mechanism remains unclear. In vitro studies suggest that podocytes have high ATP demands to maintain their structure and function, however, analyzing their ATP dynamics in living kidneys has been technically challenging. Here, using intravital imaging to visualize a FRET-based ATP biosensor expressed systemically in female mice due to their suitability for glomerular imaging, we monitor the in vivo ATP dynamics in podocytes during ischemia reperfusion injury. ATP levels decrease during ischemia, but recover after reperfusion in podocytes, exhibiting better recovery than in glomerular endothelial cells. However, prolonged ischemia results in insufficient ATP recovery in podocytes, which is inversely correlated with mitochondrial fragmentation and foot process effacement during the chronic phase. Furthermore, preventing mitochondrial fission via pharmacological inhibition ameliorates podocyte injury in vitro, ex vivo, and in vivo. Thus, these findings provide several insights into how ATP depletion and mitochondrial fragmentation contribute to podocyte injury after ischemic AKI and could potentially be therapeutic targets.